EULAR Scleroderma Trials and Research group statement and recommendations on endothelial precursor cells. Issue 2 (23rd July 2008) - Distler, J H W; Allanore, Y; Avouac, J; Giacomelli, R; Guiducci, S; Moritz, F; Akhmetshina, A; Walker, U A; Gabrielli, A; Müller-Ladner, U; Tyndall, A; Matucci-Cerinic, M; et al.
Abstract : Systemic sclerosis (SSc) is characterised by a progressive microangiopathy that contributes significantly to the morbidity of patients with SSc. Besides insufficient angiogenesis, defective vasculogenesis with altered numbers of endothelial precursor cells (EPCs) might also contribute to the vascular pathogenesis of SSc. However, different protocols for isolation, enrichment, culture and quantification of EPCs are currently used, which complicate comparison and interpretation of the results from different studies. The aim of the European League Against Rheumatism Scleroderma Trials and Research (EUSTAR) group expert panel was to provide recommendations for standardisation of future research on EPCs. Consensus statements and recommendations were developed in a face to face meeting by an expert panel of the basic science working group of EUSTAR. The findings were: cardiovascular risk factors and medications such as statins should be described in detail. A detailed description of methods considering isolation, culture, enrichment and detection of EPCs should be given. For in vitro culture of EPCs, no protocol has been shown to be superior to another, but coating with laminin and type IV collagen would resemble most closely the situation in vivo. The endothelial phenotype should be confirmed in all in vitro cultures at the end of the culture period. We recommend using CD133, vascular endothelial growth factor type 2 receptor (VEGFR2) and CD34 in combination with a viability marker for quantification of EPCs in the blood. Finally, exact standard operating procedures for fluorescence-activated cell sorting (FACS) analysis are given that should be strictly followed. In summary, the EUSTAR recommendations will help to unify EPC research and allow better comparison between the results of different studies.